PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA MAS AL WASHLIYAH 12 PERBAUNGAN - Iskandar Zulkarnain; Sofia Idawati Lubis (Jurnal Education and Development, 2023)
This study aimed to obtain empirical evidence about the application of the Flipped Classroom learning method in improving students' speaking skills and how students perceive learning using the Flipped Classroom learning method. This research is a quasi-experimental study with the research population of class XI students at MAS Al Washliyah 12 Perbaungan. Two classes were randomly selected from the school as the research sample, namely 35 students in class XI.2 as the control class and 35 students in class XI.1 as the experimental class. The experimental class was given treatment with the Flipped Classroom model and the control class was treated with conventional learning. The instruments used were speaking tests and questionnaires for MA students in class XI. The data were calculated using SPSS version 26. The results showed that (1) there was a significant difference between the posttest results of the experimental class students and the control class students. This is evidenced by the test results which show the significance of the final score in the experimental class 0.040 lower than 0.05 or can be formulated with 0.040 <0.05. This means that there is a significant difference in the final score between the control class and the experimental class; (2) students are happy with the application of Flipped Classroom, motivated, easier to speak in English, helped in speaking English, and can learn anywhere and anytime.